"Hit‐and‐run": Transcription factors get caught in the act. (21st May 2015) - Charoensawan, Varodom; Martinho, Claudia; Wigge, Philip A.
<x xml:space="preserve">Abstract</x> A key challenge for understanding transcriptional regulation is being able to measure transcription factor (TF)‐DNA binding events with sufficient spatial and temporal resolution; that is, when and where TFs occupy their cognate sites. A recent study by Para et al. has highlighted the dynamics underlying the activation of gene expression by a master regulator TF. This study provides concrete evidence for a long‐standing hypothesis in biology, the "hit‐and‐run" mechanism, which was first proposed decades ago. That is, gene expression is dynamically controlled by a TF that transiently binds and activates a target gene, which might stay in a transcriptionally active state after the initial binding event has ended. Importantly, the experimental procedure introduced, TARGET, provides a useful way for identifying multiple target genes transiently bound by their regulators, which can be used in conjunction with other well‐established methods to improve our understanding of transcriptional regulatory dynamics.